Elizabeth I, red rose of the House of Tudor [compact disc, unabridged] - Lasky, Kathryn (Royal diaries., 2005)
In a series of diary entries, Princess Elizabeth, the eleven-year-old daughter of King Henry VIII, celebrates holidays and birthdays, relives her mother's execution, revels in her studies, and agonizes over her father's health.